A study on the Evaluation Model of Teaching Quality of Accounting Majors under the perspective of Sports Psychology - Jing, Wu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
To improve sports psychology and service delivery among sportspeople, the basics of applied sports psychology and the teaching quality of accounting majors could be the best possible solution. In sports training centres, students interested in pursuing a career in applied sports psychology will benefit from a global perspective of training and education in the sports industry. Quality teaching can introduce the efficient and effective theory and research application into sports psychology's historical, developmental, social, and cultural roots. The teaching and coaching quality sets standards for psychologists who want to practice sports psychology to guide their training. Finally, the teaching quality in accounting majors and sports knowledge protects the sportsmen by ensuring that services are given to eligible people.